Evaluation of Health-Oriented Fitness Centres by Resigned Male Clients - Zarotis, Georgios F. (Disease and Health: Research Developments Vol. 7, 2025)
In order to be competitive and establish themselves in the market in the long term, fitness studios need sustainable innovations in terms of products and services. This is crucial because the targeted fulfillment of customer expectations leads to customer satisfaction, which in turn has a positive effect on customer loyalty and economic success. The aim of the evaluations and statistical analyses presented here is to examine the question of to what extent the evaluations of a fitness studio by men dropping out from their contract are age-dependent. In other words: do studio evaluations– that probably have played a role in the quitting decision - have a different basis in older men in relation to younger men? A total of 61 men, who had terminated their contract with a fitness studio, were questioned. The participants were asked about different aspects of the training possibilities, equipment, support and environmental factors of the fitness studio. The average age of the respondents was 44.1 years. The average duration of membership added up to 4.4 years. Overall, it is found that only a few of the reasons offered in the survey are also indicated in significant frequency as important for the quitting decision. On the whole, the various aspects of the studio offer and its surroundings were largely rated as "good", the mean values range around the value 2. The respondents particularly expressed their appreciation for opening hours, trainers (friendliness, helpfulness, competence), trial training and first impression. The membership costs and individual aspects such as music, spaciousness, ventilation, locker rooms and parking facilities are evaluated more critically, if not really badly. Regarding the respondents’ age, there are only minor evaluation differences among the age categories. These small differences in age have, depending on the item evaluated, very different directions. The collected data should help to create recommendations for action that can help to increase customer satisfaction in fitness companies and to reduce long-term drop-out rates by an adequate service offering. Customer satisfaction indicates how well the product use experience compares to the buyer’s value expectations including in fitness aspects.